Disease Patterns and outcomes of Neonatal Admissions at Raparin Pediatric Teaching Hospital in Erbil City - shaker, Norhan (Iraqi National Journal of Nursing Specialties, 2015)
Objectives: This study aims to determine the disease’s patterns and outcomes of admission among neonates hospitalized at the neonatal care unit in Erbil City, and using the findings as a baseline for neonate’s morbidity and mortality assessment in the future. Methodology: A retrospective study carried out at neonatal care unit of Raparin pediatric teaching hospital. An instrument for data collection developed by researcher included (age, gender, cause of admission, diagnosis and outcome upon discharge and causes of death). Content validity of the instrument was determined through the use of panel experts and reliability of the instrument was determined through a pilot study. The data were obtained by review the medical records of all newborns admitted to neonatal care unit during 2013. Data were analyzed through the application of descriptive and inferential statistical approaches by using Statistical Package for Social Science (SPSS) version 19. Results: During 1st January to 31st December of 2013 the total number of neonates admitted to Raparin pediatric teaching hospital was 3880. Highest percentages (58%) of neonates were male and majorities (76.26%) were admitted during the first week of life. Jaundice was the main cause 54.1% of neonates admission .The neonate deaths rate was 5.4% of the sample, and the first cause of death was for prematurity 35.6%, then infections 25.5%, congenital anomalies18.8% and Respiratory dysfunction 10.1%. Majority 87.9% of neonates were discharged with unspecified discharge outcome. And the study found high significant association between neonate’s diseases and neonate’s age. Recommendations: The study recommended improving statistical recording skills for health care team and conducting further studies regarding neonatal care at neonatal care unit of Raparin pediatric teaching hospital.